Strategi Pemasaran Berkelanjutan PT Unilever Indonesia Tbk dalam Menanggapi Tren Konsumen Ramah Lingkungan - Chika Tiara Pratiwi; Agnes Marcelina; Nadira Ardelia Putri; Tri Wahyu Utami; Yanuar Ramadhan (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze the sustainable marketing strategy implementedby PT Unilever Indonesia Tbk. in responding to the trend of environmentally friendly consumers. Increasing public awareness of environmental issues encourages companies to develop marketing approaches that are not only profit oriented, but also consider social and ecological aspects. This research uses the literature review method with a qualitative approach, by analyzing secondary sources such as scientific journals, annual reports, and the sustainability report of PT Unilever Indonesia Tbk in 2024. The results of analysis show that Unilever has carried out various strategic initiatives such as environmentally friendly product innovation, consumer education campaigns (#GenerasiPilahPlastik), as well as distribution efficiency and cost control. These strategies are proven to strengthen brand image and consumer loyalty, although challenges such as high product prices and production costs are still an obstacle. This study concludes that Unilever's sustainable marketing strategy has a positive impact on consumer perceptions, but requires continuous evaluation and innovation to achieve a balance between sustainability and longterm profitability.